ASR, Volume 16, n° 1, 2012 - Full Issue - Journal System (African Sociological Review, 2013)
Contents Editorial .....................................1 General Issues Mafeje and ‘Authentic Interlocutors’: an appraisal of his epistemology Bongani Nyoka ..................................4 Contemporary Discourses in Qualitative Research: Lessons for Health Research in Nigeria A. A. Abdullahi, A. Seneka, C. Van Zyl-schalekamp, J. Amzat & T.S. Saliman ............19 Rites et Condition Humaine : Leçon sur les leçons des pères Lamine Ndiaye................................41 Research Papers An Explorative study of Abortion Among the Tarok in Central Nigeria Titilayo Cordelia Orisaremi ...........................61 Exploitation Agricole des Berges: Une Srategie D’Daptation aux Changements Climatiques Destructrice Des Forets Galeries dans La Plaine De L’oti Badabaté Diwédiga, Komlan Batawila, Kpérkouma Wala, Koffi HounkpÈ, Apeti Koffi Gbogbo, Sêmihinva Akpavi, Thierry Tatoni & Koffi Akpagana ....................77 L’adoption des produits cosmétiques par les consommateurs camerounais: la forte incidence de la nouveauté perçue, de l’innovativité, de l’implication et des valeurs Darius Djoma and Victor Tsapi .........................100 Private Returns on Education in Ghana: Estimating the Effects of Education on Employability in Ghana Prince Asafu-Adjaye .......................................121